EFEKTIVITAS PENGGUNAAN MICROSOFT EXCEL DALAM PENGOLAHAN NILAI RAPOR SISWA SMA NEGERI 11 BONE - Nursita, Lisa; Astina, Astina; Isakasari, Isakasari; Amiruddin, Idris (Department of Islamic Education Management, 2021)
Abstract: The Effectiveness of Using Microsoft Excel in Processing Student Report Scores at SMA Negeri 11 BoneMicrosoft Excel is one of the media that is familiar and commonly used as a tool to perform data processing. This study aims to determine the teacher's perception of the effectiveness of the Microsoft Excel application as a medium for processing student report cards at SMA Negeri 11 Bone. Data collection techniques in this study used a survey with google form. The population in this study were all homeroom teachers at SMA Negeri 11 Bone. The research analysis method uses a quantitative descriptive approach, the survey uses a Likert scale and the data analysis technique is carried out descriptively by calculating the percentage of data using frequency and interval distributions, then interpreted in depth. The results showed that respondents who categorize that the use of Microsoft Excel is effectively used in processing student report cards at SMA Negeri 11 Bone. Processing student report cards using Microsoft Excel can make it easier for teachers to complete data processing on student report cards, for that training is needed to improve teacher skills in using Microsoft Excel applications. Abstrak: Efektifitas Penggunaan Microsoft Excel dalam Pengolahan Nilai Rapor Siswa SMA Negeri 11 BoneMicrosoft Excel adalah salah satu media yang familiar dan biasa digunakan sebagai alat untuk melakukan olah data. Penelitian ini bertujuan untuk mengetahui persepsi guru tentang keefektifan aplikasi Microsoft Excel sebagai media untuk melakukan olah data nilai rapor siswa di SMA Negeri 11 Bone. Teknik pengumpulan data dalam penelitian ini menggunakan survei dengan google form. Sampel dalam penelitian ini yaitu semua wali kelas yang ada di SMA Negeri 11 Bone. Metode analisis penelitian menggunakan pendekatan deskriptif kuantitatif, survei menggunakan Skala Likert dan teknik analisis dengan menghitung persentase data menggunakan distribusi frekuensi dan interval, kemudian dinterpretasi secara mendalam. Hasil penelitian menunjukan bahwa responden yang mengkategorikan bahwa penggunaan Microsoft Excel efektif digunakan dalam pengolahan nilai rapor siswa di SMA Negeri 11 Bone. Pengolahan nilai rapor siswa dengan menggunakan Microsoft Excel dapat mempermudah guru dalam menyelesaikan olah data nilai rapor siswa, untuk itu dibutuhkan pelatihan untuk meningkatkan kemampuan guru dalam menggunakan aplikasi Microsoft Excel.